2001
DOI: 10.1110/ps.47601
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a deletion mutant of human thymidylate synthase Δ (7–29) and its ternary complex with Tomudex and dUMP

Abstract: The crystal structures of a deletion mutant of human thymidylate synthase (TS) and its ternary complex with dUMP and Tomudex have been determined at 2.0 Å and 2.5 Å resolution, respectively. The mutant TS, which lacks 23 residues near the amino terminus, is as active as the wild-type enzyme. The ternary complex is observed in the open conformation, similar to that of the free enzyme and to that of the ternary complex of rat TS with the same ligands. This is in contrast to Escherichia coli TS, where the ternary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 30 publications
6
82
0
Order By: Relevance
“…The Ca RMSD values between the liganded and unliganded mTS structures presented here, as well as between these structures and the crystal structures of other ternary complexes with dUMP and Tomudex, including those with hTS [15,16], rTS [17] and mTS [18], are shown in Table 3. The superimposition of the mTS, mTS-dUMP and mTS-FdUMP-meTHF structures is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ca RMSD values between the liganded and unliganded mTS structures presented here, as well as between these structures and the crystal structures of other ternary complexes with dUMP and Tomudex, including those with hTS [15,16], rTS [17] and mTS [18], are shown in Table 3. The superimposition of the mTS, mTS-dUMP and mTS-FdUMP-meTHF structures is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This region has not been reported to be involved in 5-FdUR resistance; structural analysis indicates that it is located on the active site pocket and interacts with folate-based inhibitors, providing a plausible rationale for resistance (1, 11-16). The N-terminal residues from Gly 5 through Gln 18 accumulated 10 substitutions; this segment is disordered in existing crystal structures and has no known function (11)(12)(13)(14)(15)(16). There is no obvious correlation between the frequency of either single or multiple substitutions observed in resistant mutants and the presence of ␤-sheets or ␣-helices.…”
Section: Distribution Of Pcr-generated Mutations Yielding 5-fdurmentioning
confidence: 99%
“…Among these site-directed replacements is T51S, the most common mutation we have previously observed and present in the highly resistant variant T51S, G52S (6). Thr 51 participates in hydrogen bonding within the Arg 50 loop and with Val 313 after ligand-induced conformational changes of the C-terminal segment (1,(11)(12)(13)(14)(15)(16); 5-FdUR resistance could arise at Thr 51 from several mechanisms, including an effect on this conformational change. Two replacements at Asp 254 (D254N and D254E) were observed in multiply mutated variants (255, 318, 358), and we found that both, as well as the D254A substitution, conferred resistance as single mutations (Fig.…”
Section: -Fdur-resistant Thymidylate Synthase Mutantsmentioning
confidence: 99%
See 2 more Smart Citations